The study of flavonoids and glycosides in the Digitalis lanata - Pozsonyi, Kinga (Acta Biologica Szegediensis, 2002)
The population of Digitalis lanata was studied in hillocks of Pécs-Nagyárpád, the southern part of Transdanubia in Hungary. The qualitative analysis of digitalis-glycosides and flavonoids in the leaves of naturally growing Digitalis lanata was carried out. The qualitative analysis was carried out by TLC. The digitalis-glycoside content was smaller in the leaves of naturally growing Digitalis lanata than in the leaves of cultivated variations.